Analysis of The Effectiveness of the Bekasi Regional Government’s Communication Strategy in the Dissemination of Regional Regulation Number 2 of 2025 Concerning Waste Management - Bayu Dio Iman Nugraha; Fahmi Andri Adi; Edison Bonar Tua Hutapea (PT. Student Rihlah Indonesia, 2026)
Waste management in Bekasi Regency has become an urgent challenge due to the increasing population and industrialization, which have exceeded the capacity of available landfills. As a strategic response, the Bekasi Regency Government enacted Regional Regulation (Perda) Number 2 of 2025 concerning waste management. This research aims to analyze and empirically measure the influence of the political communication strategy of the local government on the effectiveness of socializing this regulation. This study employs a quantitative explanatory approach using a survey method. Data were collected through questionnaires distributed to 100 respondents selected via stratified random sampling from three representative districts: East Cikarang, Kedung Waringin, and Central Cikarang. In this study, the independent variables include Message Delivery, Media Selection, Frequency of Socialization, and Communicator Credibility, while the dependent variable is the Effectiveness of Socialization, which is measured by the levels of public knowledge and participation. The results of the inferential statistical analysis indicate that message delivery, media selection, socialization frequency, and communicator credibility have a significant positive effect on socialization effectiveness. Communicator credibility and media selection exert the most dominant influence on public understanding. This study offers a novel perspective by integrating the dimensions of political communication into waste management policies in a highly industrialized region. The policy implications suggest that the Bekasi Regency Government must shift from conventional top-down dissemination to a more participatory approach, utilizing digital media and optimizing local community leaders to enhance public compliance and long-term environmental sustainability.